Assistance in the Implementation of Organizational Management Ideology as a Forum for Aisyiyah Branch Management Leadership - Nur Busyra; D. Made Darmawati; Ervin Azhar; Muhamad Alimudin (TAAWUN, 2025)
This community service activity aims to strengthen the understanding of Muhammadiyah ideology and increase the managerial and organizational communication capacity of the management of the Jatisampurna Bekasi Branch. This step was taken in response to the weak organizational structure and low digital literacy among the new management. The method used is a collaborative and multidisciplinary approach, through three stages: preparation, implementation, and evaluation. This activity includes ideological refreshment, and organizational management training. The results of the activity showed a significant improvement in the understanding of ideology, organizational structure, internal communication, and the ability to design work programs in each assembly. Pre-test and post-test evaluations showed an increase in understanding of up to 95% of various indicators. The usefulness of this activity lies in the transformation of Leader of the 'Aisyiyah Branch management into agents of change that are resilient, religious, and adaptive to the challenges of the digital era. This activity model can be replicated as a sustainable and innovative community-based women's organization empowerment strategy.